2016
DOI: 10.1016/j.apsusc.2015.10.090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the reactive atmosphere on the formation of nanoparticles in the plasma plume induced by nanosecond pulsed laser irradiation of metallic targets at atmospheric pressure and high repetition rate

Abstract: International audienceThe influence of a reactive atmosphere on the formation of nanoparticles (NPs) in the plasma plume generated by nanosecond pulsed laser irradiation of metal targets (Ti, Al, Ag) was probed in-situ using Small Angle X-ray Scattering (SAXS). Air and different O2-N2 gas mixtures were used as reactive gas within atmospheric pressure. SAXS results showed the formation of NPs in the plasma-plume with a mean radius varying in the 2-5 nm range. A decrease of the NPs size with increasing the O2 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We assume that the generation of these NPs occurs in the plasma phase, while secondary particles are the result of a partial condensation and agglomeration of this material during the bubble evolution. Recently, it has been shown that the formation of NPs in the laser-induced plasma, does not occur only during laser ablation in liquids, but it also occurs in ambient gas environment [4,5], further sustaining the hypothesis that NPs formation takes place during plasma evolution.…”
Section: Introductionmentioning
confidence: 86%
“…We assume that the generation of these NPs occurs in the plasma phase, while secondary particles are the result of a partial condensation and agglomeration of this material during the bubble evolution. Recently, it has been shown that the formation of NPs in the laser-induced plasma, does not occur only during laser ablation in liquids, but it also occurs in ambient gas environment [4,5], further sustaining the hypothesis that NPs formation takes place during plasma evolution.…”
Section: Introductionmentioning
confidence: 86%
“…Unfortunately,t he spatiala nd temporal resolution of the SAXS experiments does not allow confirming the formation of the smallest NPs in plasma phase. In any case other authors [20,21] have already supposed that in the laser induced plasma produced in gas environment, NPs formation begin in the plasma phase. Considering that, as ac onsequence of the higher density,t he plasma induced in water has got more suitable condition for the growth of NPs with respecto f plasma induced in gas, it can be supposedt hat this phenomenon occurs also in our experiments.…”
Section: Nanoparticles Produceda Th Igh Water Pressuresmentioning
confidence: 98%
“…Some usefuli nformation have been obtained by SAXS experiments performed in air and in water [19,20] as well as by theoreticalm odels. The correlation between the effect induced by the pressure on both the plasma and the cavitation bubble with the produced NPs is used to retrievei nformationa bout the role playedb yt hem on the NPs formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is attributed to the change in the number of faces exposed on the surface. Moreover, the influence of a reactive atmosphere on the formation of Ag, Ti, and Al NPs during the rapid thermal annealing realized with the use of nanosecond pulsed irradiation was investigated by Girualt et al 32 For experiments conducted at the lowest concentration of O 2 (only 1 vol % of O 2 ), the size of Al NPs and Ti NPs was equal to ca. 5 nm, whereas in the O 2 −N 2 gas mixture (15 vol % of O 2 ) decreases to 1.9 and 3.4 nm, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%